2017
DOI: 10.1021/acs.energyfuels.7b02440
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the Preparation of Meso- and Microporous Canola Stalk-Derived Hydrothermal Carbon via Response Surface Methodology for Methylene Blue Removal

Abstract: In this work, design of experiments–response surface methodology (RSM) was implemented to predict the importance of hydrothermal carbonization (HTC) key parameters and their interactions in the preparation of canola-stalk-derived hydrochar via HTC technique. According to the RSM results, temperature and reaction time were found to be the most important control factors. The possible optimum conditions were found to be 207 °C and 82 min for temperature and time, respectively, in order to achieve a hydrochar with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 86 publications
(195 reference statements)
0
17
0
Order By: Relevance
“…The experimental procedure for HTC has been described in detail before. 31 Briefly, each HTC process is comprised of mixing CAWL (carbon source), S. platensismicroalgae (nitrogen source), and deionized water in a 100 mL stainless steel Teflon-lined hydrothermal synthesis autoclave reactor (Figure 1, Supporting Information Video). Three grams of CAWL powder was mixed with the appropriate amount of microalgae based on the required microalgae/biomass weight ratio.…”
Section: Introductionmentioning
confidence: 99%
“…The experimental procedure for HTC has been described in detail before. 31 Briefly, each HTC process is comprised of mixing CAWL (carbon source), S. platensismicroalgae (nitrogen source), and deionized water in a 100 mL stainless steel Teflon-lined hydrothermal synthesis autoclave reactor (Figure 1, Supporting Information Video). Three grams of CAWL powder was mixed with the appropriate amount of microalgae based on the required microalgae/biomass weight ratio.…”
Section: Introductionmentioning
confidence: 99%
“…The extent of the surface area revealed that the HTC process leads to a low porosity-based material. However the value obtained was slightly higher than that for hydrochar prepared from canola stalk by HTC at 207ºC for 82 min (2.69 m 2 •g -1 ) [26]. Tran et al [20] prepared hydrochar from golden shower at 190ºC for 24 h, which produced a surface area (24.80 m 2 •g -1 ) almost three times higher than the precursor (8.14 m 2 •g -1 ), which was due to the weak decomposition of cellulose and lignin during the HTC process.…”
Section: Samplementioning
confidence: 57%
“…The broad band at 3200-3600 cm -1 corresponds to the stretching vibration of O-H groups from the phenol groups of hemicellulose, cellulose, and lignin and N-H stretching vibration [31]. However, the hydroxyl peak in the MOPF was stronger than in the hydrochar due to the organic acid content in the biomass consisting of carboxyls, phenols and/or chemisorbed water [19,30] and due to the removal of the H and O from the hydrochar due to the dehydration and decarboxylation processesduring the formation of H 2 O and CO 2 as liquid products [26]. C-H stretching in the aliphatic CH, CH 2 , and CH 3 groups and aromatic C=C bending (due to the aromatic characteristic of lignin) are apparent at the bands at 2920 cm -1 and 1620 cm -1 , respectively.…”
Section: Samplementioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays, the membrane-based liquid desiccant air dehumidification which had been mostly applied in wastewater treatment processes has become more interesting for researchers worldwide, who are investigating the field of air conditioning systems [12]. This technology, which is a thermally driven separation process, utilizes the vapor pressure difference across the porous membrane as a driving force to achieve successful separation and dehumidification [13]. The most important difference between this method and the conventional liquid desiccant air dehumidification is the utilization of semi-permeable membranes for the separation of the processing air and liquid desiccant fluids which generally results in the successful inhibition of liquid from penetrating [14].…”
Section: Introductionmentioning
confidence: 99%